Malondialdehyde determination in raw and processed meat products by UPLC-DAD and UPLC-FLD. (15th November 2019) - Bertolín, J.R.; Joy, M.; Blanco, M.
Highlights: Malondialdehyde was determined in raw and processed meat products. A method to analyze malondialdehyde by UPLC was developed. The UPLC method is simple, accurate and fast. Malondialdehyde was overestimated using the TBARS spectrophotometric method. Abstract: The objective of this study was to develop an accurate and fast method to determine malondialdehyde (MDA) levels in raw and processed meat. This method is based on extraction with trichloroacetic acid (TCA), reaction with 2-thiobarbituric acid (TBA) and quantification with ultraperformance liquid chromatography with a fluorescence detector (UPLC-FLD) with ʎexcitation  = 530 nm and ʎemission  = 550 nm and with a diode array detector (UPLC-DAD) with ʎabsorbance  = 532 nm. The method tested was compared with the TBARS spectrophotometric method with ʎabsorbance  = 532 nm. The concentration of MDA was similar for most of the matrices in both UPLC methods, except for cooked ham and frankfurter sausage. The TBARS spectrophotometric method overestimated the MDA concentration in all the matrices. Therefore, the use of both chromatographic methods, especially UPLC-FLD, to determine MDA would be more advisable than the classic TBARS method to avoid overestimation in meat and processed meat products.